Hidden Histories of the Dead Disputed Bodies in Modern British Medical Research - Hurren, Elizabeth T. (Social Sciences, 2021)
This discipline-redefining study of secretive British medical research cultures after World War Two retraces the harvesting and recycling of bodies and body-parts for tissue culture and pathology labs, transplantation surgery facilities, brain banks, and dissection teaching spaces between 1945 and 2000. This title is also available as Open Access.